Glycolysis is integral to histamine‐induced endothelial hyperpermeability. Issue 3 (10th February 2021) - Ziogas, Athanasios; Sajib, Md Sanaullah; Lim, Jong‐Hyung; Alves, Tiago C.; Das, Anupam; Witt, Anke; Hagag, Eman; Androulaki, Nikolais; Grossklaus, Sylvia; Gerlach, Michael; Noll, Thomas; Grinenko, Tatyana; et al.
Abstract: Histamine‐induced vascular leakage is a core process of allergic pathologies, including anaphylaxis. Here, we show that glycolysis is integral to histamine‐induced endothelial barrier disruption and hyperpermeability. Histamine rapidly enhanced glycolysis in endothelial cells via a pathway that involved histamine receptor 1 and phospholipase C beta signaling. Consistently, partial inhibition of glycolysis with 3‐(3‐pyridinyl)‐1‐(4‐pyridinyl)‐2‐propen‐1‐one (3PO) prevented histamine‐induced hyperpermeability in human microvascular endothelial cells, by abolishing the histamine‐induced actomyosin contraction, focal adherens junction formation, and endothelial barrier disruption. Pharmacologic blockade of glycolysis with 3PO in mice reduced histamine‐induced vascular hyperpermeability, prevented vascular leakage in passive cutaneous anaphylaxis and protected from systemic anaphylaxis. In conclusion, we elucidated the role of glycolysis in histamine‐induced disruption of endothelial barrier integrity. Our data thereby point to endothelial glycolysis as a novel therapeutic target for human pathologies related to excessive vascular leakage, such as systemic anaphylaxis.